THE RELATIVE EFFECTIVENESS OF COGNITIVE RESTRUCTURING AND STUDY SKILLS TRAINING ON THE ADJUSTMENT TO ACADEMIC FAILURE AMONG A GROUP OF NIGERIAN STUDENTS (1989)
This study was intended to evaluate the relative effectiveness of two treatment strategies comprising Cognitive Restructuring (CR) and Study Skills Training(SST) with particular reference to adjustment to academic failure among a group of Nigerian students. Three groups of subjects participated in the study. Group I was exposed to CR, Group II was assigned to SST while Group III was used as Control (CT). Altogether, there were 96 subjects. The 96 subjects were grouped into three (3) equal numbers. Each group consisted of 16 internal and 16 external (I - E) subjects. Each group was further sub-divided into equal halves comprising 8 internal and 8 enternal (I - E) subjects. Thus each sub-group had 16 subjects. There were six of these sub-groups. Two were exposed to CR, two assigned to SST while the remaining two were used as Control. This sub-group of 16 subjects was desirable for treatment primarily to facilitate adequate attention from the therapist to individual subjects. It was also to afford each subject as much opportunity as possible to participate meaningfully in the group therapy. The following six (6) Instruments were used for the study: Rotter’s Locus of Control (I-E); Adeyoju1s Adjustment Problems Associated with Academic Failure Inventory, (APAWAFI); Bakare’s Student Problems Inventory, (SPI); Sarason’s General Anxiety Scale, (SGAS); Sarason and Mandeler’s Examinations Anxiety Scale and West African School Certificate and General Certicate of Education, Ordinary Level, English Language Objective Test, all of which were administered prior and after treatments. The CR therapy was administered to experimental Group I while SST was administered on experimental Group II. Group III, i.e. CT was not exposed to any of the treatment strategies. All the three groups were posttested and the data were analysed using Analysis of Covariance (ANCOVA) and tetest. Five hypotheses were tested at .05 level of significance. The results revealed were as follows: The results of hypothesis I showed that there was a significant difference in the level of academic performance of subjects in the different groups. Subjects in the treatment Groups I and II performed significantly The following six (6) Instruments were used for the study: better than those in the CT . However, subjects in Groups II who were exposed to SST performed significantly better than those in Group' I – exposed to CR. Although the two treatment strategies were effective in fostering academic performance among subjects, nevertheless, SST was more efficacious than CR (F = 3.09, df 90, p <0.5). The results of hypothesis II revealed that both treatments were effective in reducing the level of problems associated with academic failure (F= 37.90, df 90, p <0.05). The results in hypothesis III showed that there was significant reduction in the level of student problems of Groups I and II subjects exposed to CR and SST when compared with CT (F = 47.65, df 90, 9<05). The results of hypothesis IV showed that CR and SST proved effective in ameliorating the general anxiety among subjects in study situations (F =126.75, df 90, p <0.01). The results of hypothesis V revealed that CR and SST treatments led to significant reduction in the level of examination anxiety of subjects when compared with those in the CT (F =6 3.71, df 90, p < 0.01). Generally, the two treatment strategies proved effective in academic performance; reducing problems associated with academic failure; ameliorating study problems, general as well as examination anxieties among subjects. However, CR has been found to be consistently more efficacious than SST in the aforementioned psychological problems in study situations. It is therefore apparent in this study, that the cognitive domains of subjects who are being treated for adjustment to academic failure should be explored intensively and conscientiously. For instance, study skills alone had hitherto attracted much attention to the neglect of Cognitive domains of subjects. Suffice it to say that study skills training and cognitive restructuring should be simultaneously and vigorously applied in treating subjects suffering from problems of adjustment to academic failure.